A tale of two GTPases in cotranslational protein targeting - Saraogi, Ishu (Wiley Subscription Services, Inc., A Wiley Company, 2011)
Guanosine triphosphatases (GTPases) comprise a superfamily of proteins that provide molecular switches to regulate numerous cellular processes. The “GTPase switch” paradigm, in which a GTPase acts as a bimodal switch that is turned “on” and “off” by external regulatory factors, has been used to interpret the regulatory mechanism of many GTPases. Recent work on a pair of GTPases in the signal recognition particle (SRP) pathway has revealed a distinct mode of GTPase regulation. Instead of the classical GTPase switch, the two GTPases in the SRP and SRP receptor undergo a series of conformational changes during their dimerization and reciprocal activation. Each conformational rearrangement provides a point at which these GTPases can communicate with and respond to their upstream and downstream biological cues, thus ensuring the spatial and temporal precision of all the molecular events in the SRP pathway. We suggest that the SRP and SRP receptor represent an emerging class of “multistate” regulatory GTPases uniquely suited to provide exquisite control over complex cellular pathways that require multiple molecular events to occur in a highly coordinated fashion.